Effects of Elevated Carbon Dioxide on Photosynthesis and Carbon Partitioning: A Perspective on Root Sugar Sensing and Hormonal Crosstalk - Thompson, Michael; Gamage, Dananjali; Hirotsu, Naoki; Martin, Anke; Seneweera, Saman (Frontiers in Physiology, 2017)
Abstract Plant responses to atmospheric carbon dioxide will be of great concern in the future, as carbon dioxide concentrations ([CO2]) are predicted to continue to rise. Elevated [CO2] causes increased photosynthesis in plants, which leads to greater production of carbohydrates and biomass. Which organ the extra carbohydrates are allocated to varies between species, but also within species. These carbohydrates are a major energy source for plant growth, but they also act as signaling molecules and have a range of uses beyond being a source of carbon and energy. Currently, there is a lack of information on how the sugar sensing and signaling pathways of plants are affected by the higher content of carbohydrates produced under elevated [CO2]. Particularly, the sugar signaling pathways of roots are not well understood, along with how they are affected by elevated [CO2]. At elevated [CO2], some plants allocate greater amounts of sugars to roots where they are likely to act on gene regulation and therefore modify nutrient uptake and transport. Glucose and sucrose also promote root growth, an effect similar to what occurs under elevated [CO2]. Sugars also crosstalk with hormones to regulate root growth, but also affect hormone biosynthesis. This review provides an update on the role of sugars as signaling molecules in plant